Gestão de eventos: tendências sendo reveladas a partir da Pandemia da COVID-19 - Azevedo, Ana Maria Costa (Brasil, 2021)
The main objective of this work was to analyze the perceptions of professionals in the event sector about the trend and new formats of events from the Covid-19 pandemic. The proposal arose after the authors' concern about not having scientific studies that could address the theme and thus being able to scientifically contribute to the needs of reinvention of professionals. For this, bibliographical research on directed communication and event management was used, as well as documentary research on pandemic data. As a data collection instrument to obtain the necessary information about events, semi-structured interviews were used with professionals in the area and, for the analysis of information, exploratory research was used, with the purpose of qualitative interpretation of meanings. From the data obtained, it was possible to achieve the result of preparing a manual on how to organize digital events, which can be used by professionals and academics who feel the need for guidance in this period of adaptation. Thus, it was concluded that this work, together with the final product, has great relevance for the Public Relations area, for the improvement of professional practice in the events segment, by contributing to the scientific-professional aspect, thus expanding the possibilities of learning. In addition to allowing new inspiration in the execution of other formats of events for professionals in the sector.